Level structure of 72 As studied with the (α,xnp) reaction. - Mariscotti, M. A. J.; Behar, M.; Filevich, Alberto; García Bermúdez, G.; Hernandez, A. M.; Kohan, C. (North Holland Publishing, 1976)
Fil: Mariscotti, M. A. J. Comisión Nacional de Energía Atómica; Argentina